2018
DOI: 10.1002/ange.201712224
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Chemistry of the Class C Radical SAM Methyltransferase NosN by Using an Allyl Analogue of SAM

Abstract: The radical S-adenosylmethionine (SAM) superfamily enzymes cleave SAM reductively to generate ah ighly reactive 5'-deoxyadenosyl (dAdo) radical, which initiates remarkably diverse reactions.U nlike most radical SAM enzymes,t he class Cr adical SAM methyltransferase NosN binds two SAMs in the active site,using one SAM to produce ad Ado radical and the second as am ethyl donor.H ere,w e report am echanistic investigation of NosN in which an allyl analogue of SAM (allyl-SAM) was used. We showt hat NosN cleaves al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, the alkylcobalamin must be able to react with the substrate radical. The ability to generate the DOA⋅ radical from SAM analogues has been previously demonstrated for Se ‐adenosylselenomethionine ( Se SAM), SAE, allyl‐SAM, nucleobase analogues, and the sulfoxide derivative of SAH [36–38,84,85] . Alkylcobalamins have been described in some studies, including enzyme‐catalysed C−C bond formation [86,87] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the alkylcobalamin must be able to react with the substrate radical. The ability to generate the DOA⋅ radical from SAM analogues has been previously demonstrated for Se ‐adenosylselenomethionine ( Se SAM), SAE, allyl‐SAM, nucleobase analogues, and the sulfoxide derivative of SAH [36–38,84,85] . Alkylcobalamins have been described in some studies, including enzyme‐catalysed C−C bond formation [86,87] …”
Section: Resultsmentioning
confidence: 99%
“…This suggests that these analogues do not support radical generation with QCMT. Recently, it has been shown that allyl‐SAM can be a functional analogue in radical SAM enzymes [37] . However, steric restraints might impede allyl‐SAM binding to the FeS‐cluster of QCMT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15−17 More recently, we showed that NosN is able to cleave allyl-SAM, a SAM analogue in which the methyl group is replaced by an allyl group. 18 Lin, Hoffman, and coworkers showed that several SAM analogues, in which the 3amino-3-carboxylpropyl group of SAM was modified, can be cleaved by Dph2, 19−21 an unconventional radical SAM enzyme involved in diphthamide biosynthesis. 22 However, to date, the tested SAM analogues are all confined to sulfonium salts, and it remains unclear whether the substrate scope of radical SAM enzymes can be expanded beyond sulfoniums.…”
mentioning
confidence: 99%